PENGAPLIKASIAN PENGGUNAAN MICROSOFT OFFICE SEBAGAI MEDIA PENGAJARAN DAN PEMBELAJARAN BAGI GURU DI SMKS MANDIRI BOJONGGEDE BOGOR - Neny Rosmawarni; Rifka Dwi Amalia; Zatin Niqotaini (Jurnal Abdimas Bina Bangsa, 2023)
This community service (PKM) aims to examine the introduction of Microsoft Office as a teaching and learning medium at SMKS Mandiri Bojonggede, Bogor. The methods used are surveys and interviews to evaluate the use and benefits of Microsoft Office in an educational context. PKM results show that the use of Microsoft Office has great potential in improving the quality of teaching and learning at SMKS Mandiri Bojonggede. Teachers use it to create interactive presentations, manage learning materials, and create assignments and exams. While students use applications such as Word, Excel, and PowerPoint to do assignments, create reports, and present PKM results. The use of Microsoft Office as a medium of teaching and learning provides benefits in the form of improving technology skills, collaboration between teachers and students, increasing creativity in material delivery, and preparing students for the technological world of work. Despite challenges such as limited technology accessibility, lack of training for teachers, and limited understanding of students' potential applications, it is recommended to provide regular training for teachers, improve technology infrastructure, and develop teaching strategies that meet student needs. In conclusion, the introduction of Microsoft Office as a teaching and learning medium at SMKS Mandiri Bojonggede, Bogor, has a positive impact in improving student learning experience and teacher teaching effectiveness. By addressing existing challenges, the use of Microsoft Office can continue to be improved and integrated in school curricula to enhance innovative and relevant learning in the era of information technology